The Concept Of Religious Coexistence In Islām - M.R.F. Afra; M.M.A. Abdullah (MAQOLAT: Journal of Islamic Studies, 2023)
In today's globalized world, when different religious communities meet and overlap more frequently than ever before, the idea of religious cohabitation is of utmost importance. One of the most significant faiths in the world, Islam, offers a complex viewpoint on religious harmony that is based on its guiding ideals and past examples. This essay examines the complex facets of religious coexistence in Islam, diving into verses from the Quran, prophetic traditions (Hadith), and historical instances that shed light on the religion's perspective on coexisting peacefully with followers of other faiths. The analysis shows that Islam encourages a perspective on cohabitation based on the rights to one's beliefs, tolerance, and acceptance of differences between individuals, as well as social justice, humanitarianism, and brotherhood. Ultimately, a thorough comprehension of the idea of religious tolerance in Islam helps to promote tranquil, accepting societies where people of many faiths can cohabit. The teachings and ideas from Islam's approach to religious cooperation remain relevant for creating a more peaceful global community as civilizations become diverse and interconnected.